THE USAGE OF TABOO WORD TO PORTRAY THE POLITICAL VIEWS IN EMINEM SONGS LYRICS FROM 2002-2017 - Anita Rahayu; Waladdin Panggabean (Faculty of Letters Universitas Balikpapan, 2024)
This research of taboo word in the Eminem song lyrics from 2002-2017. There are two objectives of this research; 1). To identify the type of taboo word that are used to portray the political views in Eminem song lyrics and 2). To describe how the taboo words, portray political views in Eminem songs. The theory used in this research is the sociolinguistics theory according to Battistella theory of taboo word; the methodology employed is qualitative research in which the researcher tried to present the issues descriptively. As for the data, they were collected from the lyrics of the songs. The singer utterance in the song lyrics were taken out as the primary data. The result of the research, the researcher found the types of taboo word that used in Eminem song are epithet, profanity, vulgarity and obscenity. Meanwhile, the researcher also found that there are two classifications of taboo words that portray political views, taboo words portrayed protest against government’s system and taboo words portrayed protest against racial discrimination.